Effects of levosimendan on heart failure in normotensive patients: Does loading dose matter?. (March 2015) - Palmerini, Elisabetta; Söderberg, Stefan; Mondillo, Sergio; Favilli, Roberto; Lunghetti, Stefano
Abstract Background: Levosimendan is a calcium sensitizer and K+-ATP channel opener with inotropic and vasodilatatory effects irrespective of myocardial oxygen consumption, used for treatment of heart failure (HF). A loading dose is usually given by infusion for 12 h; however, profound lowering of blood pressure often disrupts or prolongs the infusion. The aim of this study was to assess clinical, biochemical and myocardial differences between different regimes of levosimendan therapy, with or without loading dose, and compared to standard therapy in heart failure. Methods: Fifty-seven patients (mean age ± SD: 60.9 ± 9.3 years, 45 males) with HF, New York Heart Association (NYHA) III–IV, reduced left ventricular ejection fraction (LVEF) were included. Twenty patients (NB group) were given levosimendan without loading dose, 14 patients (B group) were given levosimendan with loading dose, and 23 patients (C group) were given standard therapy. Clinical, biochemical and echocardiographic characteristics at baseline and one week after treatment were evaluated. Results: Groups were similar at baseline. After one week NHYA class (P < 0.001), NT pro-BNP (P < 0.001), LVEF (P = 0.045), E/A (P = 0.048) E/eʹ (P < 0.001), and PAPs (P < 0.001) decreased. DT (P = 0.011) and TAPSE (P = 0.035) increased in all groups. Conclusions: Levosimendan, as well as standard therapy, improves myocardial function and symptoms of HF, irrespective of the loading dose administration. Treatment options for patients with end-stage heart failure refractory to conventional medical therapy are limited. Inotropic drugs play an important role in heart failure (HF) (1–3).